1992
DOI: 10.1111/j.1398-9995.1992.tb05092.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of mite Dermatophagoides farinae allergen‐specific IgG and IgG subclass distribution in patients on immunotherapy

Abstract: House dust mite D. farinae and Der f II‐specific IgG and IgG subclass responses were evaluated in 32 adults with perennial rhinitis undergoing immunotherapy for 1 year by means of IgG‐RAST and ELISA. The ELISA method, which is based on subclass‐specific monoclonal antibodies, could detect 0.5–1.5 ng/ml of specific antibodies. D. farinae and Der f II‐specific IgG4 antibodies increased continuously as immunotherapy proceeded, while total IgG and IgG1 antibodies reached a plateau value 6 months after the start of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
2
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 30 publications
(11 reference statements)
3
14
2
2
Order By: Relevance
“…The change in most of these in vitro parameters was 15-100-fold for patients of the HDI group, in contrast to other studies of SIT with mites, in which the change observed was 3-10-fold (42)(43)(44). We observed a great difference between both groups of patients, according to the maintenance doses reached.…”
Section: Discussioncontrasting
confidence: 81%
“…The change in most of these in vitro parameters was 15-100-fold for patients of the HDI group, in contrast to other studies of SIT with mites, in which the change observed was 3-10-fold (42)(43)(44). We observed a great difference between both groups of patients, according to the maintenance doses reached.…”
Section: Discussioncontrasting
confidence: 81%
“…After allergen desensitization therapy, clinical improvements and a decrease in immediate and late phase skin reactivity sometimes correlate with a long-term (over 12 months) rise in specific IgG, particularly IgG4, and a decrease in specific IgE. In the short term (over 3 months), specific IgE and IgGl may rise [2]. However, there are numerous studies in which humoral changes do not correlate with clinical outcome, and the role of immunoglobulin isotypes in the protective or pathological immune response to allergens is poorly understood.…”
Section: Immunological Objectives Of Allergy Immunotherapymentioning
confidence: 93%
“…En las últimas dos décadas, se han llevado a cabo varios estudios aleatorios controlados en los cuales se ha demostrado que un porcentaje importante de los pacientes con dermatitis atópica se puede beneficiar con esta terapia, aunque su impacto varía de acuerdo con la gravedad de la enfermedad (57)(58)(59)(60)(61). En un estudio en Medellín, Colombia, se observó que los pacientes con dermatitis moderada según la puntuación en el Scoring Atopic Dermatitis (SCORAD), tuvieron una mayor y más significativa reducción de los síntomas en comparación con el grupo placebo, así como un aumento significativo de la IgG4 (62) y una disminución en la capacidad de activación de los basófilos (25), lo que indicaría una disminución sostenida de la reacción inflamatoria.…”
Section: Dermatitis Atópicaunclassified